POLA KOMUNIKASI BARETONG DALAM PROSESI PERNIKAHAN ADAT KABUPATEN PADANG PARIAMAN SUMATERA BARAT - Tiara Andesti; Yuliani Rachma Putri (Dialektika, 2017)
Baretong is an activity that mention money given by big family, people around, and invited guests. Janang Alek (the chairman) will be a center in the whole of baretong activity. This research has a purpose to find out communication patterns that used between Janang Alek, bride’s family, people around and also invited guests in that wedding reception. Theories that used in this research was activity communication to describe the communication pattern that happened in Baretong. This research used descriptive qualitative method and constructivism paradigm. Result of this research is communication patterns that happend is centralized communication patterns where we can find out the role of a chairman that leads baretong activity.